Metallic nanoislands on graphene: a metamaterial for chemical, mechanical, optical, and biological applications. Issue 6 (21st August 2017) - Marin, Brandon C.; Ramírez, Julian; Root, Samuel E.; Aklile, Eden; Lipomi, Darren J.
Abstract : Two current applications of metal nanoisland–graphene composites are shown. Abstract : Graphene decorated with metallic nanoparticles exhibits electronic, optical, and mechanical properties that neither the graphene nor the metal possess alone. These composite films have electrical conductivity and optical properties that can be modulated by a range of physical, chemical, and biological signals. Such properties are controlled by the morphology of the nanoisland films, which can be deposited on graphene using a variety of techniques, including in situ chemical synthesis and physical vapor deposition. These techniques produce non-random (though loosely defined) morphologies, but can be combined with lithography to generate deterministic patterns. Applications of these composite films include chemical sensing and catalysis, energy storage and transport (including photoconductivity), mechanical sensing (using a highly sensitive piezroresistive effect), optical sensing (including so-called "piezoplasmonic" effects), and cellular biophysics ( i.e. sensing the contractions of cardiomyocytes and myoblasts).